2011
DOI: 10.1007/978-3-642-20161-5_60
|View full text |Cite
|
Sign up to set email alerts
|

AutoEval: An Evaluation Methodology for Evaluating Query Suggestions Using Query Logs

Abstract: Abstract. User evaluations of search engines are expensive and not easy to replicate. The problem is even more pronounced when assessing adaptive search systems, for example system-generated query modification suggestions that can be derived from past user interactions with a search engine. Automatically predicting the performance of different modification suggestion models before getting the users involved is therefore highly desirable. AutoEval is an evaluation methodology that assesses the quality of query … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Our first evaluation method, AutoEval [4], is based on the idea that we can assess the quality of a domain model by comparing suggestions derived from the model to query modifications actually observed in the log files. We use Mean Reciprocal Rank (MRR) to measure this.…”
Section: Automatic Evaluation Method: Autoevalmentioning
confidence: 99%
See 1 more Smart Citation
“…Our first evaluation method, AutoEval [4], is based on the idea that we can assess the quality of a domain model by comparing suggestions derived from the model to query modifications actually observed in the log files. We use Mean Reciprocal Rank (MRR) to measure this.…”
Section: Automatic Evaluation Method: Autoevalmentioning
confidence: 99%
“…As a reminder, the relation between two terms in the model is purely some form of association link that has been extracted from the logs and is therefore different from (and complementary to) the use of semantically encoded relations as used, for example, in the Europeana project 4 , or the use of controlled vocabularies, e.g. [18,10] Using such an internal representation allows numerous potential display and interrogation techniques to be presented to the user.…”
Section: The Domain Modelmentioning
confidence: 99%
“…The validity of the framework has been confirmed with a user study [2]. The evaluation is performed on arbitrary intervals, e.g.…”
Section: The Evaluation Frameworkmentioning
confidence: 77%
“…We use an automated evaluation framework, AutoEval, which measures the effectiveness of query recommendations over a period of time based on actual query logs [2]. The evaluation framework was validated with a user study which showed that scores from the automated evaluation correlated highly with user evaluation of the recommendations.…”
Section: Evaluation Methodologymentioning
confidence: 99%